Preparation and Properties of RDX/Aluminum Composites by Spray-Drying Method. (4th November 2020) - Sun, Hongyan; Li, Xiaodong; Wu, Pengfei; Song, Changgui; Yang, Yue
Abstract : RDX/aluminum composites were prepared by the spray-drying method with F2602 as a binder. The morphology and covering effect of composites were characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The effect of the processing parameters on the morphology of the samples was investigated. The impact sensitivity and thermal decomposition behavior of RDX/aluminum composites were also measured and analyzed. Optimal morphology of samples was achieved when the inlet temperature, nitrogen flow rate, and suspension feed flow rates were 80°C, 473 L·h -1, and 4.5 mL·min -1, respectively. In addition, RDX/aluminum composites with the same content were prepared by a coverage-mixing method for comparative analysis. Experimental results showed that the thermal sensitivity and the impact sensitivity of RDX/aluminum composites prepared by the spray-drying method were significantly lower than those of RDX/aluminum composites prepared by the coverage-mixing method.